Wireless electromagnetic radiation assessment based on the Specific Absorption Rate (SAR): a review case study - Abdul-Al, Mohamed; I. Amar, Ahmed S.; Elfergani, Issa; Littlehales, Richard; Parchin, Naser Ojaroudi; Al-Yasir, Yasir; Chan, Hwang See; Zhou, Dawei; Zainal Abidin, Zuhairiah; Alibakhshikenari, Mohammad; Zebiri, Chemseddine; Elmegri, Fauzi; et al. (MDPI, 2022)
Employing electromagnetic fields (EMFs) in new wireless communication and sensing technologies has substantially increased the level of human exposure to EMF waves. This paper presents a useful insight into the interaction of electromagnetic fields with biological media that is defined by the heat generation due to induced currents and dielectric loss. The specific absorption rate (SAR) defines the heating amount in a biological medium that is irradiated by an electromagnetic field value. The paper reviews the radio frequency hazards due to the SAR based on various safety standards and organisations, including a detailed investigation of previously published work in terms of modelling and measurements. It also summarises the most common techniques utilised between 1978 and 2021, in terms of the operational frequency spectrum, bandwidth, and SAR values.